Evaluación de las hojas de canchaquiro (Tournefortia Scabrida, Kunth), presentes en Mojanda (Imbabura Ecuador), como especie vegetal fijadora de nitrógeno - Burbano Burbano, Lucía Adriana (2015)
This study aimed to evaluate Canchaquiro Sheets (Tournefortia scabrida Kunth) as a contributor of nitrogen through the same physical chemistry evaluation also incorporate the stubble on a test cultivation of beans (Phaseolus vulgaris L.). The results indicate that fallen leaves of Canchaquiro (Tournefortia scabrida Kunth), provide nutrients to the soil, so it could be used as a fertilizer for crops, if you are looking to improve the initial soil characteristics. The present study was based on the application of fallen leaves of Canchaquiro (Tournefortia scabrida Kunth) in three treatments tested, where it was observed that the organic matter in the soil increased 2.99% to 3.26% at T0 and T2 Nitrogen 0.15% increased to 0.16% respectively. While in bean plants (Phaseolus vulgaris L.) increased 74.82% to 77.47% for organic matter, and nitrogen increased 3.47% to 4.52% at T0 and T2 respectively, showing that the incorporation of Canchaquiro (Tournefortia scabrida Kunth) improves the nutritional characteristics of the crop. Due to the lack of research on the Canchaquiro (Tournefortia scabrida Kunth) and its ability to fix nitrogen, this work made her way in the research and production of information on the possible qualities of Canchaquiro (Tournefortia scabrida Kunth) as a natural contributor to Nitrogen, where it was evident against a culture test Frejol (Phaseolus vulgaris L.) to include it on the floor, contributes to nitrogen fixation and contribution of micro and macro nutrients to the soil.